A importância do capital social no desenvolvimento local e regional - Welter, Elton Carlos (2019)
A community develops along with a clear and long-term project, in which the actors in the society relate to each other and aim local development, based on sustainability concepts. The major challenge of local and regional economic development is to find methods that optimize the sustainability of natural resources, guaranteeing adequate environments for future generations. The objective of this study was to analyze the fish farming of the municipality of Maripá, located in western Paraná, which proved to be successful in the diversification of the agricultural sector, in which social capital was determinant in the articulation of the productive chain, and consequently, there was the adjustment of public policies, both for credit and technical assistance. The study evaluated the action of fish farmers and social agents in fish farming, analyzing their growth on a temporal and quantitative scale, evaluating the main factors influencing the activity, such as organization, technical assistance, credit, industrialization and the articulation between these variables. The results showed a great growth and intensification of the fish culture, due to the great density of data that promoted synergy and reliability between all the actors involved in the productive chain. Therefore, there is a medium and long-term planning, which promotes local and regional development, making Maripá a regional reference in fish farming. It is concluded that this analysis, applied in a fish farming activity, can be used as a methodological alternative to promote studies about local development in other places and activities.